Islam Sebagai Pedoman Menghadapi Perubahan Dalam Hidup - Muhammad Putra Ramadhan Nasution; Figo Erwanda; Ferdi Syaifullah; Erdiansyah Erdiansyah; Fitria Mayasar; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islam as a comprehensive religion offers life guidelines that not only regulate spiritual aspects, but also social, economic and cultural aspects. In facing the changes that continue to occur in life, both at the individual and societal levels, Islam provides basic principles that can be used as a basis for navigating the challenges of the times. This material examines how Islamic teachings, through the Al-Qur'an, Hadith, and ijtihad, provide guidance on how to respond to dynamic change. The main focus in this discussion is how Muslims can maintain a balance between steadfastness in religious principles and flexibility in facing the progress of the times, without losing their identity as devout people. By prioritizing a deep understanding and relevance of Islamic teachings in a modern context. The aim of this research is to provide insight for Muslims so that they can make Islam a solid guide in facing all forms of change, both in aspects of personal and social life. The method used in this research is a qualitative method, by using books, magazines, articles and journals related to the research theme to collect data, then codify them, and then describe them in this article. The results of this research show that Islam emphasizes the importance of steadfastness in the basic principles contained in the Al-Qur'an and Hadith, which do not change over time. These principles include justice, compassion, moral integrity, and self-development through knowledge and worship. It is hoped that this understanding will be able to strengthen the spiritual, moral and social resilience of Muslims in an increasingly complex and global life.